2023
DOI: 10.1021/acsami.3c03829
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Transparent Electronic Skin Sensor with Sensing Capabilities for Pressure, Temperature, and Humidity

Abstract: Inspired by the interlocked biological geometry of human skin, herein, we design a flexible and transparent sensor with interlocked square column arrays with composites of Ag nanoparticles (AgNPs), citric acid (CA), and poly(vinyl alcohol) (PVA), which exhibit multisensory capabilities for pressure, temperature, and humidity. As a flexible pressure sensor, the interlocked AgNPs/CA/PVA sensor possesses a high sensitivity (−1.82 kPa–1), low detection limit (10 Pa), fast response (75 ms), and outstanding stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…As shown in Figure 5h, when a finger was rapidly pressed on and off the sensor, the response and recovery times were 100 and 70 ms, respectively, which are closer to the response time of human skin (30−50 ms), indicating a low hysteresis. 56 A comparison of the sensitivity and sensing range of the sensors reported in the previous work 13,15,22,26,34,36,39,[41][42][43]54 is given in Figure 5i, where it is found that the AgNPs/TPU pressure sensor had a relatively higher sensitivity and wider detection range. For a clearer comparison, the sensitivity and detection range of various microstructured sensors are given in Table S2.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As shown in Figure 5h, when a finger was rapidly pressed on and off the sensor, the response and recovery times were 100 and 70 ms, respectively, which are closer to the response time of human skin (30−50 ms), indicating a low hysteresis. 56 A comparison of the sensitivity and sensing range of the sensors reported in the previous work 13,15,22,26,34,36,39,[41][42][43]54 is given in Figure 5i, where it is found that the AgNPs/TPU pressure sensor had a relatively higher sensitivity and wider detection range. For a clearer comparison, the sensitivity and detection range of various microstructured sensors are given in Table S2.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…The microstructures in these sensors can usually be fabricated by specific methods such as laser-scribing, bionic replica, template transfer, , and screen printing . Combined with other related research reports, it can be seen that these microstructure preparation processes can lead to improvements in sensor sensitivity and detection range .…”
Section: Introductionmentioning
confidence: 99%
“…5 For example, exible electronic sensors can convert physiological activity signals into visible electrical signals through signal conduction, which has great application prospects in the elds of human clinical diagnosis, humancomputer interaction, 6 articial intelligence robotics, 7 and exible electronic skin. [8][9][10] In particular, exible sensors can be used for multifunctional sensing, such as pressure and temperature sensing, [11][12][13][14][15] through the thermoelectric, piezoelectric, and friction electric properties of the materials. Ionic gels with dual stimulated temperature and pressure responsive materials are expected to provide an idea for the construction of temperature and pressure sensors.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 However, conventional commercial electronic temperature sensors require heavy energy supply systems and are vulnerable to electromagnetic interference. 13 Compared to the electronic counterpart, optic-based temperature sensors exhibit the advantages of being non-contact and having higher sensitivity and low detection limits. 14 With the merits of having small mode volumes, high quality (Q) factors and high integration capability, 15 whisper-ing-gallery-mode (WGM) microresonators are excellent platforms in the fields of nonlinear optics, 16 low threshold lasing, 17 on-chip optical communication 18 and miniature sensing.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 However, conventional commercial electronic temperature sensors require heavy energy supply systems and are vulnerable to electromagnetic interference. 13 Compared to the electronic counterpart, optic-based temperature sensors exhibit the advantages of being non-contact and having higher sensitivity and low detection limits. 14…”
Section: Introductionmentioning
confidence: 99%